FINANCIAL REDISTRIBUTION AMONG THE BUDGETS OF TYUMEN, YAMAL, AND YUGRA: DISTINCTIVE ASPECTS - Valerij V. Gamukin (Север и рынок: формирование экономического порядка, 2024)
The socio-economic conditions in the North of Russia exert a significant influence on financial relations. Of particular importance is the unique budgetary mechanism within the complex constituent entities of the Russian Federation, exemplified by the Tyumen region and its autonomous districts. This macro-region presents a distinctive case of financial redistribution among subjects, which is governed by the Cooperation program. The objective of this article is to elucidate the nuances of financial redistribution among the constituent entities of Russia within the 2015-2025 timeframe under the framework of horizontal budgetary control outlined in the Cooperation program. The primary redistribution trajectories include the reallocation of financial resources, specifically corporate income tax, from the North, where it is generated, to the South, where it is utilized, and their partial return in the form of budgetary investments, provision of public services, and other intragovernmental transactions to the budgets of autonomous districts. In recent years, a notable shift has been observed, involving the abandonment of spending on capital construction and an increase in other intragovernmental transactions. A direct correlation has been identified between the funding allocated to the program and the redistribution coefficient. This coefficient is proposed to be calculated as the ratio of other intragovernmental transactions to the corporate income tax going into the Tyumen region’s budget from the territories of autonomous districts. Should the trend of substituting budgetary investments and public services provision with other intragovernmental transactions persist, it raises the possibility of a modification in the program’s format or a reassessment of its funding source. The presented case study of horizontal financial redistribution among regions may offer valuable insights for Far East regions with a similar sectoral structure, characterized by a predominant extractive sector in the economy. Elements of this financial redistribution mechanism could prove beneficial within the integration processes in the new regions of Russia.